Weight Function Methods in Fracture Mechanics Theory and Applications - Wu, Xue-Ren.; Xu, Wu.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book provides a systematic and standardized approach based on the authors$1 (Bover 30 years of research experience with weight function methods, as well as the relevant literature. Fracture mechanics has become an indispensable tool for the design and safe operation of damage-tolerant structures in many important technical areas. The stress intensity factor$1 (Bthe characterizing parameter of the crack tip field$1 (Bis the foundation of fracture mechanics analysis. The weight function method is a powerful technique for determining stress intensity factors and crack opening displacements for complex load conditions, with remarkable computational efficiency and high accuracy. The book presents the theoretical background of the weight function methods, together with a wealth of analytical weight functions and stress intensity factors for two- and three-dimensional crack geometries; many of these have been incorporated into national, international standards and industrial codes of practice. The accuracy of the results is rigorously verified, and various sample applications are provided. Accordingly, the book offers an ideal reference source for graduate students, researchers, and engineers whose work involves fracture and fatigue of materials and structures, who need not only stress intensity factors themselves but also efficient and reliable tools for obtaining them.s
Part I Theoretical Background of Fracture Mechanics Weight Function Methods -- Standardized Analytical Weight Function Method Based on Crack Opening Displacements -- Analysis and Discussions of Weight Function Methods Based on Multiple Reference Load Cases -- Accuracy Verifications of Various Weight Functions and Method Assessments -- Part II Weight Functions and Stress Intensity factors for Various Crack Geometries -- Center Crack(s) in Single Connected Domain -- Edge Crack(s) in Single Connected Domain -- Edge Crack(s) in Multiple Connected Domain -- Weight Function Method and Applications to Orthotropic Composite Material -- Weight Function Method and Fracture Analysis for Plates with Multiple Cracks -- Analytical Weight Functions and Mixed Mode Stress Intensity Factors for Mode II Cracks -- Weigh Functions for Three-dimensional Crack Problems -- Part III Various Engineering Applications of Weight Function Methods -- Weigh Function Analysis of Crack Problems with Thermal/Residual Stresses -- Computation of Crack Opening Displacements/Areas with Weigh Function Methods -- Analysis of Bridging, Cohesive Model and Crack Opening Stress with Weigh Function Methods -- Weigh Functions and Stress Intensity Factors for Complex Crack Geometry -- Application of Weigh Function Methods to Multiple Site Damage Analysis -- Determination of Un-cracked Stresses Using Inverse Weight Function Method -- Appendix.
Keywords: Mechanics, Applied; Solids; Aerospace engineering; Astronautics; Mechanical engineering; Solid Mechanics; Aerospace Technology and Astronautics; Mechanical Engineering; Fracture mechanics; Strains and stresses